Diseño de la estructura organizacional y perfiles de puestos en ferretería jocar - Barreno Baidal, Diana Isabel (2015)
The Hardware Jocar is a trading company with more than 21 years dedicated to the sale of hardware, this gives credit to its customers both in the city and other cities, in order to contribute to the benefit of the same from a viewpoint of the development of the entire organization. The methodology to be used involve claims about the population, while object-method claim and determined. Therefore, the method used narrows and defines what relevant knowledge is. It allows the development of a proposal for a viable business model, or a possible solution, whose purpose is to satisfy a need or solve a problem. The hardware has the resources, financial, technical and human resources required to operate within its business scope, but in the last three years has been presenting lack of strategic planning and organizational process that includes studies to support the creation of manuals that allow optimal development of the activities performed in the company. This research aims to take the necessary corrective measures to ensure that there is a better distribution of functions, optimizing the time, so you may have more credibility in sales and thus increase their economic returns. If the organizational structure is designed and produced a manual register of documentary style features, profiles and officials within the departments and personnel working in the company, there will be a suitable organizational structure; and a valuable tool that defines activities, responsibilities and functions; thereby increasing the efficiency of workers in the organization and achieve the goals set in planning……